1994
DOI: 10.1111/j.1528-1157.1994.tb01796.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise, Stressful Life Experience, and Depression in Adults with Epilepsy

Abstract: Adults with epilepsy completed self-report measures of exercise participation, barriers to exercise, stressful life experience, depression, and general psychosocial adjustment (n = 133) as part of routine outpatient visits. Descriptive statistics showed lower levels of depression among patients who exercised regularly. Structural equation analyses confirmed the fit of a path model that included significant direct effects of exercise and stressful life experience on depression. These effects were independent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(62 citation statements)
references
References 38 publications
3
53
0
6
Order By: Relevance
“…Consistent with this, mood disturbances are more prevalent among sedentary rather than physically active individuals 27 . In this regard, Roth et al 15 analyzed the effect of physical activity on depression levels in adults with epilepsy and found that active individuals were less depressed compared to sedentary individuals. Recently, de Lima et al 16 demonstrated that people with juvenile myoclonic epilepsy presented higher levels of mood disturbances when compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this, mood disturbances are more prevalent among sedentary rather than physically active individuals 27 . In this regard, Roth et al 15 analyzed the effect of physical activity on depression levels in adults with epilepsy and found that active individuals were less depressed compared to sedentary individuals. Recently, de Lima et al 16 demonstrated that people with juvenile myoclonic epilepsy presented higher levels of mood disturbances when compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of C and TLE groups on the Profile of Mood States (POMS) scores domains. activity is a non-pharmacological therapy which can provide health benefits such as reduction in the risk of cardiovascular and endocrine diseases, improvement in bone and muscle conditioning 25 , and prevention of psychological and emotional disturbances 10,15,17,26 . Consistent with this, mood disturbances are more prevalent among sedentary rather than physically active individuals 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Exercise programs for people with epilepsy appear to decrease the common comorbidities of anxiety and depression and improve quality of life, although the longest intervention study lasted only 12 weeks. [15][16][17] Despite incomplete information, discussions and guidance about exercise remain an important part of the transition process. During school age in many countries, exercise and sports are part of the school curriculum.…”
Section: Exercisementioning
confidence: 99%
“…In a study of a teenage clinic, 207 patients (aged [11][12][13][14][15][16][17][18][19][20][21][22] were referred with "definite or probable epilepsy." 3 Epilepsy was the eventual diagnosis in 173 (84%).…”
Section: Review Of Diagnosismentioning
confidence: 99%